Standing Stock of Macrobrachium spp. in Lubuk Siam Lake - Novita, Desy; Fauzi, Muhammad; Fajri, Nur El (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Macrobrachium spp. (Palaemonidae) is commonly inhabit the Lubuk Siam Lake. A research aims to understand the standing stock, relative growth rate and recruitment pattern of the shrimp in the Lubuk Siam Lake. This study was conducted in March 2018. The shrimp was captured using bamboo traps, 4 times, once/ week. The standing stock was analyzed using DeLury method, while the relative growth rate and recruitment were analyzed using FISAT II software. Results shown that the standing stock of shrimp was 4,174. The asimtot length of growth rate (L∞) ofmale was119.28 mm, K 0.39 and t0-0.0225. The L∞ of female was 108.89 mm, K 1.8 and t0-0.0057. Recruitment percentagein March 7.17% and the highest predicted recruitment is in July (14.46%). Keywords :stock, delury, grow rate, recruitment